Pengaruh Akuntabilitas, Transparansi Dan Responsivitas Terhadap Kualitas Laporan Keuangan Kecamatan Tulungagung Kabupaten Tulungagung - Violinda Dhina Widaningrum; Firda Zulfa Fahriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of accountability, transparency and responsiveness on the quality of financial reports in Tulungagung. In this study, primary data collected by using Google form and quantitativeemethods. The populationsin this study were villagesadministrative officer throughout the Tulungagung. By calculating the Slovin formula, it generates 69 samples of individual respondent. With a significance of 0.684 and tcount of 0.409, the findings show that partially the accountability variable has no effect and is not significant on the quality of financial statements. Partially, transparency affects the quality of financial reports and significantly influences it with a significance of 0.000 and tcount of 5.589. With a significance of 0.003 and tcount 3.071 the responsiveness variable partially affects the quality of financial reports. Accountability, transparency and responsiveness all affect the quality of financial statements simultaneously and have a significant influence on it with a significance of 0.000 and Fcount of 45.995. In conclusion, the quality of financial reports in Tulungagung District, Tulungagung Regency is influenced by the transparency and responsiveness variables, while the accountability variable has no effect. Simultaneously accountability, transparency, and responsiveness affect the quality of financial reports in Tulungagung. Keywords: Accountability, Transparency, Responsiveness, Financial Report Quality